Blended cement composition
Patent Information
- Application Number
- JP2024215277
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-02-14
AI Technical Summary
【0007】 本発明の混合セメント組成物によれば、高炉スラグ微粉末及び石灰石粉末を使用することで、セメントクリンカ粉末の使用量を相対的に少なくすることができ、強度発現性に優れ、かつ、セメントクリンカの原料の一部として廃棄物等を用いることによって、セメントクリンカ粉末中の全アルカリ量(Na2O+0.658K2O)の割合が大きいにも関わらず、流動性の低下の程度が小さい混合セメント組成物を得ることができる。
Smart Images

Figure 2025023352000001 
Figure 2025023352000002 
Figure 2025023352000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a blended cement composition. [Background technology]
[0002] Currently, as part of measures to combat global warming, the cement manufacturing industry is being called upon to significantly reduce carbon dioxide emissions. Most of the carbon dioxide emissions in the cement manufacturing industry are generated during the production of cement clinker, and in order to reduce carbon dioxide emissions, there is a demand to reduce the production volume of cement clinker. As a cement that can reduce the amount of cement clinker used, blast furnace cement, in which part of the cement clinker powder is replaced with ground granulated blast furnace slag, is known. Patent Document 1 describes a cement composition using ground granulated blast furnace slag, which contains at least the following components (a), (b), and (c) in the following ratios: (a) Cements containing gypsum and ground cement clinker having a hydraulic ratio (HM) of 2.0 to 2.4, a silicate ratio (SM) of 1.3 to 3.0, and an iron ratio (IM) of 1.5 to 3.0: 20 to 50% by mass (b) Blaine specific surface area is 5,000 cm 2 / g or more blast furnace slag powder: 30 to 70 mass% (c) Limestone powder: more than 0% by mass to 40% by mass
[0003] On the other hand, in recent years, the production volume of coal ash, which has been used as a raw material for cement clinker, has been decreasing due to the decrease in coal-fired power generation. Therefore, biomass ash has been attracting attention as a raw material for cement clinker to replace coal ash. In addition, examples of raw materials for cement clinker that have been used traditionally include waste materials such as construction soil, municipal waste incineration ash, and sewage sludge. Biomass ash and the above waste materials contain more alkali than coal ash. Therefore, when the above biomass ash or the like is used as a substitute for coal ash, which is a raw material for cement clinker, there is a problem that the amount of alkali in the produced cement clinker becomes large. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2012-254909 A Summary of the Invention [Problem to be solved by the invention]
[0005] Although ground granulated blast furnace slag has excellent qualities as a material to be mixed with cement, its production volume is not so large, and it is expected to become insufficient in the future. Therefore, there is a demand for cement that can reduce the amount of cement clinker powder used by replacing part of the cement clinker powder with a material other than ground granulated blast furnace slag. Furthermore, if the amount of alkali contained in the raw materials of cement clinker becomes large, there is a problem in that alkali sulfates are produced in the cement containing the cement clinker, reducing the fluidity of the cement. The object of the present invention is to provide a mixed cement composition which can reduce the amount of cement clinker powder used, has excellent strength development, and exhibits a small degree of decrease in fluidity despite a large proportion of total alkali (Na2O+0.658K2O) in the cement clinker powder by using waste materials and the like as part of the raw materials of the cement clinker. [Means for solving the problem]
[0006] As a result of intensive research into solving the above problems, the present inventors have found that the above objects can be achieved by a mixed cement composition in which, relative to a total amount of 100 mass% of cement clinker powder, ground granulated blast furnace slag, and limestone powder, the proportion of cement clinker powder is 47 to 62 mass%, the proportion of ground granulated blast furnace slag is 22 to 46 mass%, the proportion of limestone powder is 4 mass% or more and less than 12 mass%, and the proportion of total alkali (Na2O+0.658K2O) in the cement clinker powder is 1.3 to 2.0 mass%, and have completed the present invention. That is, the present invention provides the following [1] to [4]. [1] A powdery mixed cement composition comprising cement clinker powder, ground granulated blast furnace slag, and limestone powder, wherein, in a total amount of 100% by mass of the cement clinker powder, ground granulated blast furnace slag, and limestone powder, the proportion of the cement clinker powder is 47 to 62% by mass, the proportion of the ground granulated blast furnace slag is 22 to 46% by mass, the proportion of the limestone powder is 4% by mass or more and less than 12% by mass, and the proportion of the total alkali content (Na2O+0.658K2O) in the cement clinker powder is 1.3 to 2.0% by mass. [2] The mixed cement composition according to [1], wherein the cement clinker powder contains an aluminate phase in an amount of 7 to 17 mass % and an alite phase in an amount of 51 to 63 mass %. [3] The mixed cement composition according to [1] or [2], wherein the proportion of gypsum in the mixed cement composition is 1.0 to 5.0 mass% in terms of SO3. [4] The mixed cement composition according to any one of [1] to [3], wherein the molar ratio (total alkali amount / SO3) of the total alkali amount (Na2O+0.658K2O) in the cement clinker powder to the SO3 in the cement clinker powder is 0.4 to 1.2. [5] A hydraulic composition comprising the mixed cement composition according to any one of [1] to [4] above, water, and an aggregate. Effect of the Invention
[0007] According to the mixed cement composition of the present invention, by using ground granulated blast furnace slag and powdered limestone, the amount of cement clinker powder used can be relatively reduced, and a mixed cement composition having excellent strength development and a small degree of decrease in fluidity can be obtained, even though the proportion of total alkali (Na2O+0.658K2O) in the cement clinker powder is large, by using waste materials and the like as part of the raw materials for the cement clinker. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The mixed cement composition of the present invention is a powdery mixed cement composition containing cement clinker powder, ground granulated blast furnace slag, and limestone powder, in which, relative to a total amount of 100 mass% of the cement clinker powder, ground granulated blast furnace slag, and limestone powder, the proportion of the cement clinker powder is 47 to 62 mass%, the proportion of the ground granulated blast furnace slag is 22 to 46 mass%, the proportion of the limestone powder is 4 mass% or more and less than 12 mass%, and the proportion of the total alkali content (Na2O+0.658K2O) in the cement clinker powder is 1.3 to 2.0 mass%. In this specification, the term "mixed cement composition" refers to a composition containing cement clinker powder, which is made by mixing a plurality of types of powdery materials.
[0009] In the total amount of cement clinker powder, ground granulated blast furnace slag, and limestone powder (100% by mass), the proportion of cement clinker powder is 47-62% by mass, preferably 48-61% by mass, more preferably 49-60% by mass, and particularly preferably 49.5-59.5% by mass. If the proportion is less than 47% by mass, the strength development is reduced. If the proportion is more than 62% by mass, the amount of cement clinker powder in the mixed cement composition is increased, and the effect of reducing the amount of cement clinker powder used and reducing the carbon dioxide emission associated with clinker production is reduced.
[0010] The proportion of the aluminate phase (3CaO·Al2O3) in the cement clinker powder is preferably 7 to 17 mass %. The above ratio can increase the waste material unit (the proportion of waste-derived raw materials in the cement composition can be increased by using more waste as a clinker raw material) and, from the viewpoint of improving early strength development, is preferably 7 mass% or more, more preferably 8 mass% or more, even more preferably 9 mass% or more, and particularly preferably 12 mass% or more. In addition, from the viewpoint of further improving the fluidity and workability of mortar and the like containing the mixed cement composition, the above ratio is preferably 17 mass% or less, more preferably 16 mass% or less, even more preferably 15 mass% or less, and particularly preferably 13 mass% or less.
[0011] The proportion of alite (3CaO·SiO2) in the cement clinker powder is preferably 51-63 mass%, more preferably 51.5-62 mass%, and particularly preferably 52-61 mass%. If the proportion is 51 mass% or more, the early strength development is further improved. If the proportion is 63 mass% or less, the fluidity and workability of mortar containing the mixed cement composition are further improved. The proportion of belite (2CaO SiO2) in the cement clinker powder is preferably 10 to 22 mass%, more preferably 12 to 21 mass%, and particularly preferably 14 to 20 mass%, from the viewpoint of strength development, etc. If the proportion is 10 mass% or more, the long-term strength development is further improved. The proportion of the ferrite phase (4CaO·Al2O3·Fe2O3) in the cement clinker powder is preferably 7 to 20 mass %, more preferably 8 to 15 mass %, and particularly preferably 9 to 12 mass %, from the viewpoint of strength development and the like.
[0012] In this specification, the proportions of the aluminate phase, alite, belite, and ferrite phase in the cement clinker powder are calculated as percentages in the total amount (100 mass%) of the cement clinker powder based on the chemical components of the cement clinker raw materials and the cement clinker (burned product) using the following Bogue's calculation formulas (1) to (4). (1) Alite (mass %) = (4.07 x CaO (mass %)) - (7.60 x SiO2 (mass %)) - (6.72 x Al2O3 (mass %)) - (1.43 x Fe2O3 (mass %)) (2) B-lite (mass%)=(2.87×SiO2(mass%))-(0.754×C3S(mass%)) (3) Aluminate phase (mass%)=(2.65×Al2O3(mass%))-(1.69×Fe2O3(mass%)) (4) Ferrite phase (mass%) = 3.04 × Fe2O3 (mass%)
[0013] As the raw material for cement clinker, it is possible to use raw materials generally used in the production of cement clinker. Specifically, it is possible to use CaO raw materials such as limestone, quicklime, and slaked lime, silicon-containing raw materials such as silica stone and clay, aluminum-containing raw materials such as clay, and iron-containing raw materials such as iron slag and iron cake. In addition to the above raw materials, one or more materials selected from industrial waste, general waste, and construction waste soil can be used as part of the raw materials. These waste materials usually contain substances containing alkali metals such as sodium and potassium. Here, industrial waste refers to waste generated as a result of business activities. Examples of industrial waste include raw concrete sludge, various sludges (e.g., sewage sludge, water purification sludge, steel sludge, etc.), construction waste, concrete waste, various incineration ashes (e.g., coal ash, chicken manure ash, livestock manure ash, biomass ash, sludge incineration ash), foundry sand, rock wool, waste glass, secondary blast furnace ash, various by-products, and unused resources (materials that remain unused, etc.). Municipal waste refers to waste other than industrial waste. Examples of general waste include dried sewage sludge, municipal waste incineration ash, and shells.
[0014] The proportion of total alkali (Na2O + 0.658K2O) in the cement clinker powder is 0.7 to 2.0 mass%. From the viewpoint of increasing the amount of waste material used as the raw material for cement clinker, the above ratio is preferably 0.8% by mass or more, more preferably 0.9% by mass or more, even more preferably 1.0% by mass or more, and particularly preferably 1.3% by mass or more. From the viewpoint of further improving the fluidity and workability of mortar or the like containing the mixed cement composition, the above ratio is preferably 1.9% by mass or less, more preferably 1.8% by mass or less, even more preferably 1.7% by mass or less, and particularly preferably 1.6% by mass or less. In addition, the molar ratio of the total alkali amount (Na2O+0.658K2O) in the cement clinker powder to the SO3 in the cement clinker powder (total alkali / SO3) is preferably 0.4 to 1.2, more preferably 0.6 to 1.1, even more preferably 0.7 to 1.0, and particularly preferably 0.8 to 1.0. If the molar ratio is 0.4 or more, the amount of waste material used as the raw material for the cement clinker can be increased. If the molar ratio is 1.2 or less, the amount of alkali dissolved in the cement clinker can be reduced, and the initial strength of the mixed cement composition can be prevented from decreasing.
[0015] As a method for producing cement clinker, the above-mentioned raw materials are mixed so that the ratios of the aluminate phase, alite, belite, and ferrite phase in the resulting cement clinker are each desired, and the resulting mixture is fired preferably at 1,200 to 1,600°C, more preferably at 1,350 to 1,500°C. The lump-like cement clinker obtained by burning is appropriately pulverized into powder form using a pulverizing means such as a ball mill. In order to adjust the ratio of the total alkali content (Na2O+0.658K2O) in the cement clinker powder to fall within a desired numerical range, an alkali metal-containing substance (e.g., a reagent such as NaOH, KOH, Na2SO4, or K2SO4) may be added to lump cement clinker or powdered cement clinker, and the mixture may be ground or mixed to prepare a cement clinker powder. Specifically, examples of the method include a method in which the aggregated cement clinker obtained by burning and the alkali metal-containing substance are simultaneously crushed and mixed, and a method in which the powdered cement clinker after crushing is mixed with the alkali metal-containing substance.
[0016] The Blaine specific surface area of the cement clinker powder is preferably 2,000 to 6,000 cm 2 / g, more preferably 2,500 to 5,000 cm 2 / g, and more preferably 2,800 to 4,000 cm 2 / g, and particularly preferably 3,000 to 3,500 cm 2 / g. The Blaine specific surface area is 2,000 cm 2 If the Blaine specific surface area is 6,000 cm / g or more, the strength development is further improved. 2 / g or less, the fluidity and workability of mortar and the like containing the mixed cement composition are further improved.
[0017] In the total amount of cement clinker powder, ground granulated blast furnace slag, and limestone powder (100% by mass), the proportion of ground granulated blast furnace slag is 22-46% by mass, preferably 23-45.5% by mass, more preferably 28-45% by mass, and particularly preferably 32-45% by mass. If the proportion is less than 22% by mass, the strength development decreases. If the proportion exceeds 46% by mass, the effect of reducing the amount of ground granulated blast furnace slag used by using another component (limestone powder) instead of ground granulated blast furnace slag decreases.
[0018] An example of the ground granulated blast furnace slag is pulverized granulated slag obtained by quenching with water and crushing molten slag, which is a by-product of pig iron production in a blast furnace. The ground granulated blast furnace slag preferably has a basicity of 1.7 or more, more preferably 1.75 or more, and particularly preferably 1.8 or more. If the basicity is 1.7 or more, the strength development is further improved. The basicity is calculated using the following formula (5). Basicity = [(CaO + MgO + Al2O3) / SiO2] (5) (The chemical formula in the formula represents the content (%) of the compound represented by the chemical formula in the ground granulated blast furnace slag.)
[0019] The Blaine specific surface area of the ground granulated blast furnace slag is preferably 3,000 to 7,000 cm 2 / g, more preferably 3,500 to 6,000 cm 2 / g, and particularly preferably 4,000 to 5,000 cm 2 / g. The Blaine specific surface area is 3,000 cm 2 If the Blaine specific surface area is 7,000 cm 2 / g or less, the fluidity and workability of mortar and the like containing the mixed cement composition are further improved.
[0020] In the total amount of cement clinker powder, ground granulated blast furnace slag, and limestone powder (100% by mass), the proportion of limestone powder is 4-23% by mass, preferably 5-21% by mass, more preferably 6-20% by mass, even more preferably 8-18% by mass, and particularly preferably 12-16% by mass. If the proportion is less than 4% by mass, the effect of reducing the amount of ground granulated blast furnace slag used by using another component (limestone powder) instead of ground granulated blast furnace slag is reduced. If the proportion exceeds 23% by mass, the strength development decreases.
[0021] The content of calcium carbonate in the limestone powder is preferably 90% by mass or more, more preferably 95% by mass or more. If the content is 90% by mass or more, the strength development is further improved. The limestone powder may be crushed limestone, or may be carbonated powder of ready-mixed concrete sludge or concrete. These powders can fix carbon dioxide gas that would normally be released into the atmosphere.
[0022] The Blaine specific surface area of the limestone powder is preferably 3,000 to 20,000 cm 2 / g, more preferably 3,500 to 18,000 cm 2 / g, and more preferably 4,000 to 15,000 cm 2 / g, and more preferably 4,200 to 10,000 cm 2 / g, and particularly preferably 4,500 to 9,500 cm 2 / g. The Blaine specific surface area is 3,000 cm 2 If the Blaine specific surface area is 20,000 cm 2 / g or less, the fluidity and workability of mortar and the like containing the mixed cement composition are further improved.
[0023] The proportion of the total amount of cement clinker powder, ground granulated blast furnace slag, and limestone powder in the total amount (100 mass%) of the powdery mixed cement composition of the present invention is not particularly limited, but is preferably 80 mass% or more, more preferably 85 mass% or more, and particularly preferably 90 mass% or more. Examples of materials (other materials) other than cement clinker powder, ground granulated blast furnace slag, and limestone powder include gypsum and silica fume, which will be described later. The mixed cement composition may contain gypsum for the purpose of adjusting the setting time and improving workability. The proportion of gypsum in the mixed cement composition is preferably 1.0 to 5.0 mass%, more preferably 1.3 to 4.0 mass%, and particularly preferably 1.5 to 3.0 mass%, in terms of SO3, from the viewpoints of strength development and the fluidity and workability of mortar and the like containing the mixed cement composition. In addition, the ratio of gypsum to 100 parts by mass of the cement clinker powder is preferably 1.5 to 6.0 parts by mass, more preferably 2.0 to 5.5 parts by mass, and particularly preferably 2.5 to 5.0 parts by mass, in terms of SO3, from the viewpoints of strength development and the fluidity and workability of mortar and the like containing the mixed cement composition. Examples of gypsum include natural gypsum dihydrate, flue gas desulfurization gypsum, phosphate gypsum, titanic gypsum, hydrofluoric gypsum, refined gypsum, hemihydrate gypsum, anhydrous gypsum, etc. These may be used alone or in combination of two or more.
[0024] The method for producing the mixed cement composition of the present invention is not particularly limited, and examples thereof include (i) a method in which clinker, blast furnace slag, limestone, and gypsum are mixed while being simultaneously ground, and (ii) a method in which pre-ground cement (a mixture of clinker powder and gypsum), pre-ground granulated blast furnace slag, and pre-ground limestone powder are mixed. In the method (ii), the ground granulated blast furnace slag may contain gypsum (previously mixed with blast furnace slag and gypsum while simultaneously grinding). In addition, in the production of a mixed cement composition, in order to adjust the ratio of the total alkali content (Na2O+0.658K2O) in the cement clinker powder to a desired numerical range, an alkali metal-containing substance (e.g., a reagent such as NaOH, KOH, Na2SO4, or K2SO4) may be added and mixed when mixing each material of the mixed cement composition or after mixing each material. In this case, the added alkali metal-containing material is considered to be contained in the cement clinker powder.
[0025] The mixed cement composition of the present invention can be mixed with water to prepare a hydraulic composition. The hydraulic composition may contain aggregates (fine aggregates, coarse aggregates) and other materials that are mixed as needed. Examples of other materials that are mixed as needed include various additives such as water reducing agents, antifoaming agents, and shrinkage reducing agents. In the present specification, the hydraulic composition is a hardenable composition containing a cement composition and water, and includes the form of the hydraulic composition before and after hardening. Examples of the hydraulic composition include paste, mortar, and concrete. The mixed cement composition of the present invention has a compressive strength at 7 days measured by the method described in "JIS R 5201:2015 Physical Testing Methods for Cement" of preferably 33 MPa or more, more preferably 34 MPa or more, and particularly preferably 35 MPa or more. EXAMPLES
[0026] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. [Materials used] (1) Finely ground blast furnace slag; Blaine specific surface area: 4,230 cm 2 / g, density: 2.92g / cm 3 , Basicity: 1.80, corresponds to blast furnace slag powder 4000 specified in "JIS A 6206:2013 (blast furnace slag powder for concrete)" (2) Limestone powder; Blaine specific surface area: 5,130 cm 2 / g, calcium carbonate content: 95% by mass or more, density: 2.72 g / cm 3 [Production of blast furnace slag mixture] The above ground granulated blast furnace slag and gypsum (flue gas desulfurization gypsum) were mixed to produce a blast furnace slag mixture (a mixture of ground granulated blast furnace slag and gypsum) having a gypsum content of 2.0 mass% (SO3 equivalent).
[0027] [Example 1, Reference Examples 1 to 5, Comparative Examples 1 to 9] [Production of cement clinker powders A to E] Using various reagents (SiO2, Al2O3, Fe2O3, CaCO3, MgO, CaSO4·2H2O, Na2CO3, K2CO3, TiO2, CaHPO4·2H2O) as raw materials, cement clinker (a simulant of cement clinker with a high total alkali content made from waste materials) was burned in a test kiln, and then the cement clinker was pulverized in a mill to prepare cement clinker powders A to E (shown as "Clinkers A to E" in Table 1) with the mineral compositions and Blaine specific surface areas shown in Table 1. Table 1 also shows the total alkali amount of the cement clinker powders A to E and the molar ratio of the total alkali amount to SO3.
[0028] [Table 1]
[0029] A cement obtained by mixing the types of cement clinker powder and gypsum powder (hemihydrate rate: 0%) shown in Table 2, a blast furnace slag mixture, and limestone powder in the amounts shown in Table 2 was mixed to obtain a mixed cement composition. The proportion of cement clinker powder, etc. in the total amount of 100 mass% of the cement clinker powder (shown as "clinker" in Table 2), ground granulated blast furnace slag (shown as "blast furnace slag" in Table 2), and limestone powder (shown as "limestone" in Table 2) contained in the mixed cement composition, and the amount of gypsum (SO3 equivalent value) per 100 parts by mass of clinker powder are as shown in Table 2.
[0030] The compressive strength of the blended cement composition was measured at ages of 3 days, 7 days, and 28 days in accordance with the method described in "JIS R 5201:2015 Physical testing methods for cement." For each mixed cement composition, mortar was prepared according to the following procedures (i) to (v), the mortar flow value of the mortar was determined, and the loss rate was calculated using the obtained mortar flow value. (i) 20 g of water and 1,350 g of standard sand for cement strength testing (sold by the Japan Cement Association) were added to the mixing bowl of a mechanical mixer specified in 8.1(2) of "JIS R 5201:2015 (Physical test methods for cement)", and then the mixture was stirred at low speed for 1 minute using a paddle. (ii) Stirring was stopped, 675 g of the mixed cement composition was added, and the mixture was then stirred at low speed with a paddle for 30 seconds. (iii) The stirring was stopped again, and 216.3 g of water containing 4.4 g of a polycarboxylic acid-based high-performance AE water reducer (manufactured by BASF Japan, product name "Masterglenium SP8N") and 6.7 g of an antifoaming agent (a 10-fold diluted solution of product name "Nicoflex 800" manufactured by Nicca Chemical Co., Ltd.) was added, and the mixture was stirred at low speed with a paddle for 1 minute, and then stirred at high speed for an additional 3 minutes to prepare a mortar. (iv) Using the mortar immediately after preparation, the mortar flow value immediately after preparation (shown as "immediately after" in the flow value column in Table 3) was measured in accordance with the slump test in 6.3 of "JIS A 1171:2016 (Test method for polymer cement mortar)". (v) After 30 minutes had elapsed since the start of the above (i), the mortar was again charged into the mixer and mixed at high speed for 1 minute using a paddle. The mortar flow value 30 minutes after the start of the work (shown as "30 minutes after" in the flow value column in Table 3) was measured in the same manner as above (iv).
[0031] In addition, for Reference Examples 1-2, Example 1, and Comparative Examples 1-2, the mortar flow value of Comparative Example 1 was used as a reference, and the reduction rate of the mortar flow value immediately after preparation of the target Example or Comparative Example and at each time point 30 minutes after the start of work was calculated using the following formula (6). Reduction rate (%)={(reference mortar flow value−target mortar flow value of example or comparative example) / (reference mortar flow value)}×100 (6) Similarly, for Reference Examples 3 to 5 and Comparative Examples 3 to 4, the mortar flow value of Comparative Example 3 was used as the standard, and for Comparative Examples 5 to 9, the mortar flow value of Comparative Example 8 was used as the standard. Using the above formula (6), the reduction rates of the mortar flow values immediately after preparation of the target Examples or Comparative Examples and at each time point 30 minutes after the start of work were calculated. In addition, the loss rate was calculated using the obtained mortar flow value and the following formula (7). Loss rate (%) = [(Mortar flow value immediately after preparation - Mortar flow value 30 minutes after work begins) / (Mortar flow value immediately after preparation - 100)] × 100 (7) The results are shown in Table 3.
[0032] [Table 2]
[0033] [Table 3]
[0034] From Table 3, it can be seen that the mortar flow values of Comparative Examples 5 to 9 (content of limestone powder: 2.7 mass %) tend to decrease as the total alkali content in the cement clinker powder increases. In addition, it can be seen that the reduction rates of the mortar flow values of Comparative Examples 5 to 7 in Comparative Examples 5 to 9 (limestone powder content: 2.7 mass%) were 48.5 to 69.1% immediately after preparation, and 51.4 to 64.9% 30 minutes after the start of kneading. On the other hand, in Reference Examples 1-2, Example 1, and Comparative Examples 1-2 (limestone powder content: 10.6 mass%), the reduction rates of the mortar flow values in Reference Examples 1-2 and Example 1 were 4.4-38.0% immediately after preparation, and -14.8-7.2% 30 minutes after the start of kneading. From these facts, in Comparative Examples 5 to 9 (content of limestone powder: 2.7 mass%), as the total alkali content in the cement clinker powder (Comparative Example 5: 0.8 mass%, Comparative Example 6: 1.2 mass%, Comparative Example 7: 1.5 mass%, Comparative Example 9: 0.6 mass%) increases, the reduction rate of the mortar flow value becomes very large (i.e., as the total alkali content increases, the degree of decrease in fluidity increases), compared to the reference Comparative Example 8 (total alkali content in the cement clinker powder is 0.1 mass%), whereas in Reference Examples 1 to 2 and Example 1 (content of limestone powder: 2.7 mass%), the reduction rate of the mortar flow value becomes very large (i.e., as the total alkali content increases, the degree of decrease in fluidity increases). In the case of the content rate: 10.6% by mass, as the total alkali content in the cement clinker powder (Reference Example 1: 0.8% by mass, Reference Example 2: 1.2% by mass, Example 1: 1.5% by mass, Comparative Example 2: 0.6% by mass) increases compared to the reference Comparative Example 1 (total alkali content in the cement clinker powder is 0.1% by mass), the reduction rate of the mortar flow value increases, but the degree of the reduction is smaller than that of Comparative Examples 5 to 9 (content rate of limestone powder: 2.7% by mass), or the reduction rate becomes negative (larger than the mortar flow value of the reference Comparative Example 1). A similar tendency was also observed in Reference Examples 3 to 5 and Comparative Examples 3 to 4 (content rate of limestone powder: 17.9% by mass).
[0035] It is also found that the compressive strengths at each age in Reference Examples 1-2 and Example 1 (3 days: 33.0-35.0 MPa, 7 days: 43.5-43.9 MPa, 28 days: 63.6-64.0 MPa) are greater than the compressive strengths at each age in Comparative Examples 1-2 (3 days: 29.9-31.8 MPa, 7 days: 41.9-43.1 MPa, 28 days: 63.2 MPa). A similar tendency was observed in Examples 4-6 and Comparative Examples 3-4.
[0036] [Example 2, Reference Examples 6 to 10, Comparative Examples 10 to 18] [Production of cement clinker powder F~J] Cement clinker powders F to J (shown as "clinkers F to J" in Table 4) having the mineral compositions and Blaine specific surface areas shown in Table 4 were prepared in the same manner as the above-mentioned cement clinker powders A to E. Table 4 shows the total alkali amount and the molar ratio of the total alkali amount to SO3 for the cement clinker powders F to J.
[0037] [Table 4]
[0038] A cement obtained by mixing the types of cement clinker powder and gypsum powder shown in Table 5, a blast furnace slag mixture, and limestone powder were mixed in the amounts shown in Table 5 to obtain a mixed cement composition. The hemihydration rate of the gypsum was 0%. The mixed cement compositions were measured for compressive strength and mortar flow values at ages of 3 days, 7 days, and 28 days in the same manner as in Example 1, Reference Examples 1 to 5, and Comparative Examples 1 to 9. The loss rate was calculated using the obtained mortar flow values and the above formula (7). Furthermore, for Reference Examples 6 to 7, Example 2, and Comparative Examples 10 to 11, the reduction rates of the mortar flow values immediately after preparation of the target Example or Comparative Example and 30 minutes after the start of work were calculated using the mortar flow value of Comparative Example 10 as a standard, using the above formula (6). Similarly, for Reference Examples 8 to 10 and Comparative Examples 12 to 13, the mortar flow value of Comparative Example 12 was used as the standard, and for Comparative Examples 14 to 18, the mortar flow value of Comparative Example 17 was used as the standard, and the reduction rates of the mortar flow values immediately after preparation of the target Examples or Comparative Examples and 30 minutes after the start of work were calculated according to the above formula (6). The results are shown in Table 6.
[0039] [Table 5]
[0040] [Table 6]
[0041] From Table 6, it can be seen that the mortar flow values of Comparative Examples 14 to 18 (content of limestone powder: 2.6 mass %) tend to decrease as the total alkali content in the cement clinker powder increases. It is also seen that the reduction rates of the mortar flow values of Comparative Examples 14 to 16 in Comparative Examples 14 to 18 were 41.5 to 69.3% immediately after preparation, and 45.6 to 64.5% 30 minutes after the start of kneading. On the other hand, in Reference Examples 6 to 7, Example 2 and Comparative Examples 10 to 11 (limestone powder content: 5.3 mass%), the reduction rates of the mortar flow values in Reference Examples 6 to 7 and Example 2 were 14.1 to 16.2% immediately after preparation and 1.0 to 8.0% 30 minutes after the start of kneading. In addition, in Reference Examples 8 to 10 and Comparative Examples 12 to 13 (limestone powder content: 15.5 mass%), the reduction rate of the mortar flow value in Reference Examples 8 to 10 was 18.0 to 25.2% immediately after preparation, and 9.3 to 13.3% 30 minutes after the start of kneading. From these facts, in Comparative Examples 14 to 18 (content of limestone powder: 2.6 mass%), as the total alkali content in the cement clinker powder (Comparative Example 14: 0.8 mass%, Comparative Example 15: 1.2 mass%, Comparative Example 16: 1.5 mass%, Comparative Example 18: 0.6 mass%) increases, the reduction rate of the mortar flow value becomes very large (i.e., as the total alkali content increases, the degree of decrease in fluidity increases), compared to the reference Comparative Example 17 (total alkali content in the cement clinker powder is 0.1 mass%), whereas in Reference Examples 6 to 7, Example 2 and Comparative Examples 10 to 11 (content of limestone powder: 2.6 mass%), the reduction rate of the mortar flow value becomes very large (i.e., as the total alkali content increases, the degree of decrease in fluidity increases). In the case of Comparative Example 10 (total alkali content in the cement clinker powder: 0.1 mass%) as a reference, the reduction rate of the mortar flow value increases as the total alkali content in the cement clinker powder (Reference Example 6: 0.8 mass%, Reference Example 7: 1.2 mass%, Example 2: 1.5 mass%, Comparative Example 11: 0.6 mass%) increases immediately after preparation, but the degree of reduction is smaller than in Comparative Examples 14 to 18 (limestone powder content: 2.6 mass%), and it can be seen that 30 minutes after the start of kneading, the reduction rate of the mortar flow value decreases as the total alkali content increases. A similar tendency was also seen in Reference Examples 8 to 10.
[0042] In addition, the compressive strengths of Reference Examples 6 to 7 and Example 2 at ages of 3 and 7 days (3 days: 26.3 to 29.8 MPa, 7 days: 40.1 to 41.6 MPa) are greater than the compressive strengths at each age of Comparative Examples 10 to 11 (3 days: 25.8 to 25.9 MPa, 7 days: 38.8 to 39.0 MPa), and the compressive strengths at an age of 28 days (64.5 to 64.8 MPa) are comparable to the compressive strengths at an age of 28 days (64.0 to 65.7 MPa) of Comparative Examples 10 to 11. A similar tendency was also observed in Reference Examples 8 to 10 and Comparative Examples 12 to 13.
Claims
1. A powdery mixed cement composition comprising cement clinker powder, ground granulated blast furnace slag, and limestone powder, In a total amount of 100% by mass of the cement clinker powder, the ground granulated blast furnace slag, and the limestone powder, the proportion of the cement clinker powder is 47 to 62% by mass, the proportion of the ground granulated blast furnace slag is 22 to 46% by mass, and the proportion of the limestone powder is 4% by mass or more and less than 12% by mass, The total alkali content of the cement clinker powder (Na 2 O+0.658K 2 A powdery mixed cement composition, characterized in that the proportion of .O) is 1.3 to 2.0 mass%.
2. 2. The mixed cement composition according to claim 1, wherein the cement clinker powder contains 7 to 17% by mass of aluminate phase and 51 to 63% by mass of alite phase.
3. The proportion of gypsum in the mixed cement composition is SO 3 The mixed cement composition according to claim 1 or 2, which is calculated to be 1.0 to 5.0 mass%.
4. The total alkali content of the cement clinker powder (Na 2 O+0.658K 2 O) and SO in the cement clinker powder 3 Molar ratio (total alkali / SO 3 4. The mixed cement composition according to claim 1, wherein the β-
5. A hydraulic composition comprising the mixed cement composition according to any one of claims 1 to 4, water, and aggregate.
Citation Information
Patent Citations
Hydraulic cement composition
JP2001240445A
Cement clinker, cement composition, manufacturing method of cement clinker and treating method of waste containing alkali component
JP2001294455A
Cement clinker and cement composition
JP2007169084A
Neutralization-preventive high-early-strength cement composition
JP2013047153A
Method of manufacturing cement paste
JP2013103865A